Cardio-STIC (spatio-temporal image correlation) as genetic ultrasound of fetal Down syndrome - Theera Tongsong (2018)
© 2014 Informa UK Ltd. Objective: To evaluate efficacy of cardio-STIC in detection of fetal Down syndrome.Methods: Cardio-STIC volume datasets (VDS) were prospectively collected from women during 16-22 weeks, consisting of 40 VDS acquired from fetuses with Down syndrome and 400 VDS from normal fetuses. All VDS were blindly analyzed.Results: Between both groups, most dimensions were comparable but the right-sided dimensions were significantly greater in fetuses with Down syndrome. Interestingly, shortening fraction was also significantly higher in affected fetuses. Right-to-left disproportion and shortening fraction were used as cardiac markers as well as other eight structural markers to predict fetal Down syndrome. Tricuspid regurgitation had highest sensitivity (30%); followed by VSD (27.5%), right-to-left disproportion (20.0%), and echogenic intra-cardiac foci (EIF; 17.5%). If the test was considered positive in case of the presence of any cardiac marker, cardio-STIC had a detection rate of 72.5% and false-positive rate of 19.5%. Likelihood ratio of each marker for modifying priori risk was also provided.Conclusion: Cardio-STIC as genetic ultrasound for Down syndrome had a detection rate of about 70% and false-positive rate 20%. Cardio-STIC analysis can be helpful in estimation of fetal risk for Down syndrome and counseling when the prenatal diagnosis of the syndrome is made.